2019
DOI: 10.1177/1062860618822102
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Toolkits: Recommendations for Development

Abstract: A burgeoning number of toolkits dedicated to improving health care exist but development guidance is lacking. The authors convened a panel of health care stakeholders, including developers, purchasers, users, funders, and disseminators of toolkits. The panel was informed by a literature review that analyzed 44 publications and 27 toolkits. A modified Delphi process established recommendations and suggestions to guide toolkit development. The panel established 12 recommendations for content and 1 recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This toolkit is located on a VA intranet site to allow access to any VA employee who wishes to implement CC. The toolkit was built using the Agency for Healthcare Research and Quality (AHRQ) Publishing and Communications Guidelines (36) and evidencebased toolkit development recommendations (37). It includes the implementation planning guide, leadership briefings, educational materials (e.g., brochures, PowerPoint presentations with notes, FAQs, research summaries), CC templates, and standard operating procedures.…”
Section: Implementation Toolkitmentioning
confidence: 99%
“…This toolkit is located on a VA intranet site to allow access to any VA employee who wishes to implement CC. The toolkit was built using the Agency for Healthcare Research and Quality (AHRQ) Publishing and Communications Guidelines (36) and evidencebased toolkit development recommendations (37). It includes the implementation planning guide, leadership briefings, educational materials (e.g., brochures, PowerPoint presentations with notes, FAQs, research summaries), CC templates, and standard operating procedures.…”
Section: Implementation Toolkitmentioning
confidence: 99%
“…Toolkits to improve health care are ubiquitous but vary in development and content. 23 When Hsu et al 24 reported on the development of a toolkit to spread Patient-Centered Medical Home redesign, they observed that the spread of innovation in health care is difficult, leading them to select a model of change that could be customized to the clinics while centered on patient-centered standardized work. They chose Lean as their method and formed their toolkit accordingly, which is also the method reported here.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to toolkit development being unstandardized and thus highly variable. For this reason, Hempel and colleagues [39] recently provided recommendations for the content, development, and evaluation of quality improvement toolkits. Of the implementation facilitation meta-strategies in this study, it appeared site visits had a strong influence on implementation, suggesting that the interpersonal component of a facilitator-provider dyad is paramount to successful implementation.…”
Section: Discussionmentioning
confidence: 99%